Nazwy fandomów jako chrematonimy - Kuć, Joanna (Papers in Linguistics, 2019)
The analysis is concerned with names of Polish fandoms and some ambiguous properties such onyms exhibit. Due to their categorial features, names of fandoms do not form one uniform class and can thus be studied within chrematonymy, medioonymy, more strictly, netonymy. They can also be considered as sociochrematonyms, as we associate fandoms with young people using slang. Fandom is not only the name of a group of fans but also its specific identifier, which defines the character and reputation of the community of fans and confirms that they belong to a particular environment.